PYRUVATE FERMENTATION BY STREPTOCOCCUS FAECALIS - Deibel, R. H. (1964)
Deibel, R. H. (American Meat Institute Foundation, Chicago, Ill.), and C. F. Niven, Jr. Pyruvate fermentation by Streptococcus faecalis. J. Bacteriol. 88:4–10. 1964.—Streptococcus faecalis, as opposed to S. faecium, utilizes pyruvate as an energy source for growth. The fermentation is adaptive, as demonstrated by growth experiments in a casein-hydrolysate medium and the fermentation of pyruvate by cell suspensions. The principal products of pyruvate catabolism were acetoin, CO(2), and lactic, acetic, and formic acids, although carbon recoveries were low due to the formation of slime. End-product analyses suggested that both the phosphoroclastic and dismutation systems were active in pyruvate breakdown. Studies with cell-free extracts indicated a thiamine diphosphate requirement for active pyruvate catabolism. The involvement of lipoic acid in the phosphoroclastic system was investigated, and, although inconclusive results were obtained, no association of this cofactor with phosphoroclastic activity could be made.